A randomized trial of oropharyngeal airways to assist stabilization of preterm infants in the delivery room. (November 2019) - Kamlin, C. Omar F.; Schmölzer, Georg M.; Dawson, Jennifer A.; McGrory, Lorraine; O'Shea, Joyce; Donath, Susan M.; Lorenz, Laila; Hooper, Stuart B.; Davis, Peter G.
Abstract: Objective: Positive pressure ventilation (PPV) using a ventilation device and a face mask is recommended for compromised newborn infants in the delivery room (DR). Airway obstruction and face mask leak during PPV may contribute to failure of resuscitation. Using an oropharyngeal airway (OPA) may improve efficacy of mask PPV. To determine whether the use of an OPA with mask PPV in the DR during stabilization of infants <34 weeks' gestational age, reduces the incidence of airway obstruction. Intervention and measurements: An international two center unblinded randomized trial. Infants assessed by the clinical team to require PPV, were randomly assigned to receive PPV using a T Piece device with either a soft round face mask alone or in combination with an appropriately sized OPA. Resuscitation protocols were standardized. A hot-wire anemometer flow sensor measured respiratory function during the first five minutes of stabilization. The primary outcome was the incidence of airway obstruction, either complete (no gas flow) or partial (minimal gas flows resulting in expired tidal volumes <2 mL/kg). Main results: A total of 137 infants were enrolled. Obstructed inflations were more frequently observed in infants stabilized with an OPA (81% vs. 64%; p = 0.03). Partial obstruction was more common in infants stabilized with an OPA (70% vs 54%; p = 0.04). There were no differences in mortality or respiratory outcomes for the whole cohort or in gestational age subgroups. Conclusions: Airway obstruction is common in preterm infants receiving mask ventilation in the DR. Using an oropharyngeal airway significantly increases the incidence of airway obstruction. Registered clinical trial: Australian and New Zealand Clinical Trials Register; ACTRN 12612000392864.